2022
DOI: 10.14202/vetworld.2022.2172-2179
|View full text |Cite
|
Sign up to set email alerts
|

A review: Virulence factors of Klebsiella pneumonia as emerging infection on the food chain

Abstract: Health problems can be caused by consuming foods that have been processed in unsanitary conditions; hence, the study of the impact of contamination on food and its prevention has become critical. The disease caused by Klebsiella pneumoniae in food is increasing significantly every year across the world. The main factors that are essential for the virulence of K. pneumoniae are lipopolysaccharide and polysaccharide capsules. Furthermore, K. pneumoniae is capable of forming biofilms. Capsule polysaccharides, fim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…This is further complex by the fact that bacteria, such as S. pneumoniae, are surrounded by a capsule that helps the bacterium evade phagocytosis, the capsule contains polysaccharides (often including uronic acids) that provide mucoviscosity, lipopolysaccharides (LPS), adhesins, and siderophores, systems that allow the bacterium to uptake iron from the environment . In addition, some of the bacterial species included in this study, such as P.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is further complex by the fact that bacteria, such as S. pneumoniae, are surrounded by a capsule that helps the bacterium evade phagocytosis, the capsule contains polysaccharides (often including uronic acids) that provide mucoviscosity, lipopolysaccharides (LPS), adhesins, and siderophores, systems that allow the bacterium to uptake iron from the environment . In addition, some of the bacterial species included in this study, such as P.…”
Section: Resultsmentioning
confidence: 99%
“…37 This is further complex by the fact that bacteria, such as S. pneumoniae, are surrounded by a capsule that helps the bacterium evade phagocytosis, the capsule contains polysaccharides (often including uronic acids) that provide mucoviscosity, lipopolysaccharides (LPS), adhesins, and siderophores, systems that allow the bacterium to uptake iron from the environment. 18 In addition, some of the bacterial species included in this study, such as P. stuartii, P. mirabilis, P. vulgaris, P. rettgeri, and H. alvei, are known to contain virulence factors. 9,38 The present study identified 1170 nonredundant peptides corresponding to 123 different virulence factors, including proteins described to perform a role in bacterial antibiotic resistance mechanisms, aid immune evasion, or constitute toxins (Supporting Information, Data S7).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported several defining factors in pathogenic agents for virulence and toxicity, mainly including capsules, pili and siderophores, which fundamentally affect both classic and virulent strains of K. pneumoniae causing severe bacteremia, pneumonia and even meningitis in vulnerable population with compromised immunity such as the ICU patients. 10 , 47 , 48 Acquisition of virulence-associated genes in CRKP is one of the main strategies to produce highly virulent CRKP. 49 It is proposed that MDR clones would be more likely to subsequently acquire virulence genes than highly pathogenic clones that, however, would be prone to get access to resistance genes, suggesting that CRKP strains with pre-existing resistance genes might take an advantage of subsequent acquisition of virulence-associated genes, when compared to CSKP strains.…”
Section: Discussionmentioning
confidence: 99%
“…K. pneumoniae pathogenicity is also associated with certain virulence factors that help it to evade host immune surveillance, including capsules, lipopolysaccharides, exopolysaccharides, adhesins, and iron uptake systems. 10 Interestingly, continuous evolution of hypervirulence plasmids gives rise to a pathotype of hypervirulent K. pneumoniae . This type of K. pneumoniae has been increasingly reported in association with plasmid-mediated pathogenicity loci of iuc, iro, rmp A/ rmp A2, etc.…”
Section: Introductionmentioning
confidence: 99%